Determination of Formaldehyde Lizardfish (Saurida tumbil) during Freezing Storage - Tati Nurhayati; Asadatun Abdullah; Sharah Novita Sari (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2019)
Formaldehyde (FA) in fish is formed as a result of fish quality decreasing, in particular the freshness of fish. The level of fish freshness can not be increased but maintained. Quality of fish can be maintained by proper handling processes, one of them is handling with low temperatures. The purpose of this study was to determine the formation process of FA lizardfish (Saurida tumbil) during freezing storage. The treatments applied were gutted and ungutted. Observations were made every 2 weeks for 22 weeks. The parameters measured were sensoric, pH, total volatile base (TVB), trimethylamine (TMA), formaldehyde (FA) and dimethylamine (DMA). The results obtained showed that FA formed after two weeks. Levels of FA formed in gutted lizardfish are 12.96 ppm and 17.77 ppm for ungutted. Formaldehyde (FA) formation occurs when the condition of the fish is still fresh with TVB content of below 20 mg N/100 g. Dimethylamine (DMA) levels when FA is formed of 7.99 ppm for gutted lizardfish and 5.50 ppm for ungutted. Formaldehyde (FA) formation also accompanied by the increation of other decay indicators.